How Effective are Indonesia’s Public Policies in Driving Economic Growth? - Indrayanti, Wiwin; Hayati, Jurni; Waluyo, Adiet Try; Choirunnisa, Luthfi Alif Dinar (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2025)
Indonesia faces a few structural challenges that fundamentally impact the sustainability of economic growth, as evidenced by its fluctuating growth patterns. This study aims to examine the extent to which government expenditure, inflation, trade, and the budget deficit contribute to growth or act as a hindrance. The data used is an annual time series over the observation period of 1988 - 2024. This study uses the Autoregressive Distributed Lag (ARDL) analysis method to identify the long-term and short-term relationships between variables. The research results show increase in Government Expenditure directly boosting aggregate demand, although the impact is temporary. Inflation tends to depress economic growth due to weakened purchasing power and economic uncertainty. Trade contributes little to growth due to fluctuations in global commodity prices. Budget deficits can boost growth through fiscal stimulus, so that it can stimulate economic activity and increase domestic output. In the long term, government expenditure resulting in a greater increase in growth than other factors. Research findings indicate that controlling inflation and improving the quality of government spending play a crucial role in maintaining stable economic growth. Key factors in promoting sustainable growth are maintaining consistent fiscal policy, prudent budget deficit management, and strengthening trade. Indonesia menghadapi sejumlah tantangan struktural yang secara fundamental mempengaruhi keberlanjutan pertumbuhan ekonomi. Hal ini terlihat dari pola pertumbuhan yang cenderung fluktuatif. Penelitian ini bertujuan untuk melihat sejauh mana pengeluaran akhir pemerintah, inflasi, perdagangan internasional dan defisit anggaran berkontribusi dalam mendorong pertumbuhan atau justru menjadi faktor penghambat. Data yang digunakan adalah data time series pada periode 1988-2024. Studi ini menerapkan pendekatan Autoregressive Distributed Lag (ARDL) untuk mengidentifikasi hubungan jangka pendek dan jangka panjang antarvariabel. Hasil penelitian ini menunjukan peningkatan pengeluaran konsumsi akhir pemerintah secara langsung mendorong permintaan agregat meskipun dampaknya bersifat sementara. Sedangkan inflasi cenderung menekan pertumbuhan akibat melemahnya daya beli masyarakat dan ketidakpastian ekonomi. Perdagangan internasional memberikan kontribusi yang lemah karena pengaruh fluktuasi harga komoditas global. Dalam jangka panjang, pengeluaran konsumsi akhir pemerintah menghasilkan kenaikan pertumbuhan yang lebih besar dibandingkan faktor lain. Temuan penelitian menunjukan bahwa pengendalian inflasi dan peningkatan kualitas konsumsi pemerintah berperan penting dalam menjaga stabilits pertumbuhan ekonomi. Faktor kunci dalam mendorong pertumbuhan jangka panjang ialah menjaga konsistensi kebijakan fiskal yang berkelanjutan, pengelolaan defisit anggaran yang hati-hati, dan penguatan perdagangan internasional.